Joint inversion of temperature, vitrinite reflectance and fission tracks in apatite with examples from the eastern North Sea area. (21st October 2022) - Nielsen, Søren B.; Balling, Niels
Abstract: As sediment accumulation indicates basin subsidence, erosion often is understood as tectonic uplift, but the amplitude and timing may be difficult to determine because the sedimentary record is missing. Quantification of erosion therefore requires indirect evidence, for example thermal indicators such as temperature, vitrinite reflectance and fission tracks in apatite. However, as always, the types and quality of data and the choice of models are important to the results. For example, considering only the thermal evolution of the sedimentary section discards the thermal time constant of the lithosphere and essentially ignores the temporal continuity of the thermal structure. Furthermore, the types and density of thermal indicators determine the solution space of deposition and erosion, the quantification of which calls for the use of inverse methods, which can only be successful when all models are mutually consistent. Here, we use integrated basin modelling and Markov Chain Monte Carlo inversion of four deep boreholes to show that the erosional pattern along the Sorgenfrei–Tornquist Zone (STZ) in the eastern North Sea is consistent with a tectonic model of tectonic inversion based on compression and relaxation of an elastic plate. Three wells in close proximity SW of the STZ have different data and exhibit characteristic differences in erosion estimates but are consistent with the formation of a thick chalk sequence, followed by minor Cenozoic erosion during relaxation inversion. The well on the inversion ridge requires ca. 1.7 km Jurassic‐Early Cretaceous sedimentation followed by Late Cretaceous–Palaeocene erosion during inversion. No well demands thick Cenozoic sedimentation followed by equivalent significant Neogene exhumation. When data are of high quality and models are consistent, the thermal indicator method yields significant results with important tectonic and geodynamic implications. Abstract : Thermal model of Danish well Aars‐1.